2016
DOI: 10.1074/jbc.m116.721282
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle-specific G Protein-coupled Receptor Kinase 2 Ablation Alters Isolated Skeletal Muscle Mechanics and Enhances Clenbuterol-stimulated Hypertrophy

Abstract: GRK2, a G protein-coupled receptor kinase, plays a critical role in cardiac physiology. Adrenergic receptors are the primary target for GRK2 activity in the heart; phosphorylation by GRK2 leads to desensitization of these receptors. As such, levels of GRK2 activity in the heart directly correlate with cardiac contractile function. Furthermore, increased expression of GRK2 after cardiac insult exacerbates injury and speeds progression to heart failure. Despite the importance of this kinase in both the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Both GRKs and β-arrestin initiate signaling cascades, which are G protein-dependent and receptor independent, that may affect the pro-hypertrophic pathway. For example, muscle-specific GRK2 knockout enhances clenbuterol-stimulated hypertrophy [ 22 ] whereas the hypertrophic response was abrogated in mice lacking β-arrestin 1, which is the predominant β-arrestin isoform in skeletal muscle [ 23 ].…”
Section: Pro-hypertrophic Hormones and Growth Factorsmentioning
confidence: 99%
“…Both GRKs and β-arrestin initiate signaling cascades, which are G protein-dependent and receptor independent, that may affect the pro-hypertrophic pathway. For example, muscle-specific GRK2 knockout enhances clenbuterol-stimulated hypertrophy [ 22 ] whereas the hypertrophic response was abrogated in mice lacking β-arrestin 1, which is the predominant β-arrestin isoform in skeletal muscle [ 23 ].…”
Section: Pro-hypertrophic Hormones and Growth Factorsmentioning
confidence: 99%
“…GRK2 has been shown to terminate GPCR signaling by desensitizing the receptor [59]. Recent studies have demonstrated that skeletal muscle-specific GRK2 knockout substantially attenuates the force of contraction of the extensor digitorum longus muscle [60]. This genetic animal model enhanced β2-adrenergic receptor (β2-AR)-mediated muscle hypertrophy by augmenting β2-AR/Akt-mediated pro-hypertrophic signaling, thereby suggesting that GRK2-dependent GPCR regulation is significant for skeletal muscle function and diseases [60].…”
Section: Exercise Training On Rgs Proteinsmentioning
confidence: 98%
“…Recent studies have demonstrated that skeletal muscle-specific GRK2 knockout substantially attenuates the force of contraction of the extensor digitorum longus muscle [60]. This genetic animal model enhanced β2-adrenergic receptor (β2-AR)-mediated muscle hypertrophy by augmenting β2-AR/Akt-mediated pro-hypertrophic signaling, thereby suggesting that GRK2-dependent GPCR regulation is significant for skeletal muscle function and diseases [60]. Further, desensitization of β-AR by elevated GRK2 expression has been reported in hypertension or congestive heart failure [61,62].…”
Section: Exercise Training On Rgs Proteinsmentioning
confidence: 99%
“…The mechanism seems to involve the stimulation of protein synthesis through the enhancement of TORC1 activation [ 61 , 62 ]. However, hypertrophy is not always functional since a reduced normalized strength was observed [ 63 ]. In addition, nitric oxide (NO) was suggested to play a role in muscle hypertrophy via the activation of the transient receptor potential cation channel, subfamily V, member 1 (TRPV1), causing an increase in intracellular Ca 2+ levels and an increase in protein synthesis through TORC1 activation by an unknown mechanism [ 64 ].…”
Section: Anabolic Pathways Decline In Skeletal Muscle Atrophymentioning
confidence: 99%